The Unfulfilled Potential of Synthetic and Biological Hydrogel Membranes in the Treatment of Abdominal Hernias - Kenigen Manikion; Christodoulos Chrysanthou; Constantinos Voniatis (Gels)
Hydrogel membranes can offer a cutting-edge solution for abdominal hernia treatment. By combining favorable mechanical parameters, tissue integration, and the potential for targeted drug delivery, hydrogels are a promising alternative therapeutic option. The current review examines the application of hydrogel materials composed of synthetic and biological polymers, such as polyethylene glycol (PEG), polyvinyl alcohol (PVA), gelatine, and silk fibroin, in the context of hernia repair. Overall, this review highlights the current issues and prospects of hydrogel membranes as viable alternatives to the conventional hernia meshes. The emphasis is placed on the applicability of these hydrogels as components of bilayer systems and standalone materials. According to our research, hydrogel membranes exhibit several advantageous features relevant to hernia repair, such as a controlled inflammatory reaction, tissue integration, anti-adhesive-, and even thermoresponsive properties. Nevertheless, despite significant advancements in material science, the potential of hydrogel membranes seems neglected. Bilayer constructs have not transitioned to clinical trials, whereas standalone membranes seem unreliable due to the lack of comprehensive mechanical characterization and long-term in vivo experiments.